(untitled) (Bangladesh Journal of Medical Education, 2023)
Introduction: This study investigated medical students’ perception of E-learning and online assessment during Covid-19 and their suggestion to overcome the problems. Method: A total of 300 1st year medical students of Calcutta National Medical College and Rampurhat Govt. Medical College were surveyed by a pre-validated semi-structured questionnaire that was provided to the 2021-22 batch. Result: Among 242 respondents (169 at CNMC and 73 at RPHGMC)159 were males (mean age 20.14 ±2.22yrs.) and 83 were females (mean age 19.65±.1.1yrs.). 68.8% of students of both the colleges revealed that offline traditional teaching is more preferrable than e-leaning. They reported that e-learning is not much effective in practical physiology teaching. Poor network, Technical glitches and lack of communication with teachers are outlined as major barriers in online teaching. Conclusion: Students did not prefer e-teaching over face-to-face teaching during the lock down situation. Bangladesh Journal of Medical Education Vol.14(1) January 2023: 3-16